Cross-cutting and Like-minded Discussion on Social Media: The Moderating Role of Issue Importance in the (De)mobilizing Effect of Political Discussion on Political Participation. Issue 1 (1st January 2021) - Chen, Hsuan-Ting; Lin, Jhih-Syuan
ABSTRACT: Using a student survey with multistage probability sampling in Taiwan, we revisited the deliberation-participation paradox by examining the relationship between cross-cutting/like-minded discussion and online political participation, emphasizing the moderating role of issue importance and focusing particularly on the social media context and two political issues in Taiwan. We found that political ambivalence, which has been proposed as the underlying mechanism between cross-cutting exposure and participation, plays a significant mediating role. Cross-cutting discussion demobilizes participation indirectly through increasing political ambivalence, while like-minded discussion mobilizes participation indirectly through decreasing political ambivalence. More importantly, the two indirect effects are conditioned upon the level of issue importance in that the demobilizing effect of cross-cutting discussion was weakened while the mobilizing effect of like-minded discussion was strengthened when the level of issue importance increased.